Trace heavy metal ions promoted extracellular electron transfer and power generation by Shewanella in microbial fuel cells. (July 2016) - Xu, Yu-Shang; Zheng, Tao; Yong, Xiao-Yu; Zhai, Dan-Dan; Si, Rong-Wei; Li, Bing; Yu, Yang-Yang; Yong, Yang-Chun
Highlights: MFCs performance was improved by addition of trace level of Cu 2+ or Cd 2+ . Cu 2+ or Cd 2+ improved riboflavin accumulation and anodic bacterial attachment. Enhanced EET might be the underlying mechanism for MFCs performance improvement. Trace heavy metal ions addition is a practical way to improve MFCs performance. Abstract: Although microbial fuel cells (MFCs) is considered as one of the most promising technology for renewable energy harvesting, low power output still accounts one of the bottlenecks and limits its further development. In this work, it is found that Cu 2+ (0.1 μg L −1 –0.1 mg L −1 ) or Cd 2+ (0.1 μg L −1 –1 mg L −1 ) significantly improve the electricity generation in MFCs. The maximum power output achieved with trace level of Cu 2+ (∼6 nM) or Cd 2+ (∼5 nM) is 1.3 times and 1.6 times higher than that of the control, respectively. Further analysis verifies that addition of Cu 2+ or Cd 2+ effectively improves riboflavin production and bacteria attachment on the electrode, which enhances bacterial extracellular electron transfer (EET) in MFCs. These results unveil the mechanism for power output enhancement by Cu 2+ or Cd 2+ addition, and suggest that metal ion addition should be a promising strategy to enhance EET as well as power generation of MFCs.